State-private Partnership’s Experience in Infrastructure Development in Southeast Asian Countries - A. A. Rogozhin (Контуры глобальных трансформаций: политика, экономика, право, 2019)
The article provides an analysis of the specifics of infrastructure development in Southeast Asia (SEA), in particular the mechanism for financing public-private partnerships (PPPs), which are supported by governments throughout the region in order to bridge the gap in infrastructure development amid limited public resources. SEA countries need investment for infrastructure development in the amount of at least $150 billion a year to maintain their economic growth, which cannot be financed exclusively from public funds or by attracting foreign capital. In the region, only Singapore and Brunei have sufficient resources to finance the development of infrastructure they need entirely from the state budget. The focus is on the five countries in the region that are most actively using the PPP mechanism now and plan to actively resort to it in the near future: Indonesia, Malaysia, the Philippines, Thailand and Vietnam. The infrastructure system of these countries is considered, as well as factors that affect the effectiveness of PPP in region - both positive and negative. It is noted that PPPs in Southeast Asia are faced with all sorts of problems, primarily with inefficient state regulation and the institutional conditions for their implementation in PPP projects. For the active implementation of PPP in Southeast Asia, it seems appropriate to focus on the proposal of a small number of carefully prepared PPP projects that may have the necessary demonstration effect. In addition, it seems to us, the powers of national and local government departments dealing with PPPs should be widened.